Tokio Cafe in the Japanese Village at the lower end of the Pay Streak, Alaska Yukon Pacific Exposition, Seattle, 1909. - Nowell, Frank H., 1864-1950 (1909)
On verso of photograph: Tokio Cafe on what was called the Pay Streak- roast beef sandwiches 10 cents. The lower end of the Pay Streak. The promenade at the left of the picture runs along the shore of Portage Bay of Lake Union to about 15th Avenue Northeast in the extreme distance. View looking northwest. There were about eleven of these little oriental type booths running up the center of the Pay Streak. PH Coll 727.715 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number